(untitled) (Indian Journal of Hill Farming, 2022)
Many biotechnological aided reproductive methods are now utilized to manage farm animal reproductive processes. Nowadays, smart artificial reproductive technology (ART) is being created that takes into account method efficiency, animal welfare, economic efficiency and environmental health. The nanotechnology based revolution has swept across all fields of science, including farm animal reproduction, allowing for considerable advances in this field. Nanotechnology has the potential to enhance and solve numerous technical challenges confronting many forms of ART. To deliver high-quality sperm doses, technologies for sperm preservation and purification have been developed using a variety of nanomaterials. Cryopreservation causes sperm damage through oxidative stress (OS) and disrupting the plasma membrane integrity. Free radicals and OS are regularly formed during the process of cryopreservation and nanoparticles (NPs) are routinely used to guard against them. We cover current nanoparticle-based approaches for preventing cryoinjuries during sperm cryopreservation in animals in this brief review.